Instructional instrument of the NOC outcomes: control knowledge of cardiac disease for patients with heart failure - Samara Rodrigues de Alvarenga; Camila de Souza Carneiro; Vinicius Batista Santos; Rita Simone Lopes Moreira (Universidade Federal de Goias, 2015)
Heart failure (HF) is a disease that presents high levels of re-hospitalizations, in some situations caused by deficient knowledge of patients regarding the control and self-management of the disease. This study aimed to elaborate and validate the content of an instructional instrument to assess the indicators of the NOC outcome Cardiac Disease Knowledge for patients with heart failure. A content validation was conducted by the analysis of six cardiology experts, and the agreement between them was assessed by the Kappa statistic. The obtained Kappa agreement level was superior to 98% for all assessed criteria, therefore the instrument was considered valid for content. This study is fundamental for the clinical practice of nurses, as it can guide the nursing assessment for knowledge of patients with HF.